(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents and discusses the theoretical foundations and empirical findings of paralinguistics. The importance of nonverbal means in expressing emotions, social relations, cultural differences, and linguistic identities is emphasized. The article argues that paralinguistics greatly contributes to understanding and interaction between people and therefore plays an important role in various contexts such as work, therapy, media and intercultural communication.